STUDY OF THE WOOD ACOUSTIC PROPERTIES OF THE USING A MODIFIED RESONANT METHOD (Innovation in Woodworking Industry and Engineering design, 2026)
Some of the unique properties of the wood are the acoustical. Together with its elastic properties they characterize this material to a great extent. Wood is unique with its characteristic of having high elasticity and damping of the low density.This work examines the basic acoustic properties, as obtained by resonance method. Specimens of spruce wood, arranged in groups of varying density, are examined. The speed of sound, dynamic modulus of elasticity, acoustic constant and damping are set. Relations between the values of these properties in longitudinal and transverse oscillations are sought. The effect of density on the properties of the wood is established.